Policy and financing interventions supporting community managed drought resilience strategies: A case of Marsabit County, Kenya - Mogaito, Shalom Magoma; Mugalavai, Edward M.; Muyekho, Fransis N (Nairobi Journal of Humanities and Social Sciences, 2023)
Drought risk management is the function of the national government complemented by the developed systems of governance in Kenya. However, this function is clearly delineated only for institutions and misses the mark in identifying the roles of communities and strategies they apply in building resilience to drought. This paper is part of a two-part series of outcomes of a study in Marsabit county, that looked at community managed strategies that promote drought resilience. Using an evaluative research design, it highlighted the policy environment in Marsabit county, mapped the institutional structures, and identified warning strategies aligned to the policy instrument. Additionally, it sets clear financial instruments within the county that support community strategies. Finally, it maps policy gaps that hinder community resilience strategies hinging them on the existing policy and financial interventions at community level.